2017
DOI: 10.1017/age.2017.14
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change, Salinization and High-Yield Rice Production in Coastal Bangladesh

Abstract: Progressive salinization of water and soil will be increasingly severe in low-lying coastal areas as climate change proceeds. Thus, understanding the economic impacts of salinity intrusion will be essential for effective adaptation planning. This paper uses econometric analysis to predict the impact of climate-induced increases in soil salinity on high-yielding-variety rice production in coastal Bangladesh. Findings indicate an output decline of 15.6 percent in nine subdistricts where soil salinity will exceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Salinity level below 4.0 dS/m are generally not stressful for most of the plants, and beyond this level, the yield gets significantly lower as found by Dasgupta et al. (2014 , 2018) . Our study showed that the newly accreted land of the Noakhali district is much higher than that tolerance range of salinity for most crops.…”
Section: Discussionmentioning
confidence: 70%
“…Salinity level below 4.0 dS/m are generally not stressful for most of the plants, and beyond this level, the yield gets significantly lower as found by Dasgupta et al. (2014 , 2018) . Our study showed that the newly accreted land of the Noakhali district is much higher than that tolerance range of salinity for most crops.…”
Section: Discussionmentioning
confidence: 70%
“…According to the Food and Agriculture Organization of the United Nations, more than 400 million hectares of land on the major continents are affected by salt [3]. Rising salinization may reduce agricultural acreage by up to 20% per year by 2050 [4]. The amount of land in India that has been degraded by excess sodicity and salinity is estimated to be about 6.75 million hectares [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of Bangladesh, some studies have been conducted to explore the patterns and determinants of livelihood strategies of riverine households (Alam et al, 2017; Brouwer et al, 2007). In addition, similar studies have also been carried out covering on fishing communities alone by the works of Paul and Vogl (2013), Ahmed (2008), Hossain et al, (2018), Deb and Haque (2016) and Islam et al (2011). However, a study on investigating the options and determinants of LD strategies of smallholder farmers especially in southwestern part is not covered by most of these studies.…”
Section: Introductionmentioning
confidence: 99%